Pre-slaughter handling of reindeer bulls {Rangifer tarandus tarandus L.) — effects on technological and sensory meat quality, blood metabolites and muscular and abomasal lesions - Wiklund, E.; Malmfors, G.; Lundström, K.; Rehbinder, C. (Rangifer, 1996)
Forty-one reindeer bulls (age 1 1/2 years) were subjected to different pre-slaughter treatments: herding for a short distance to a grazing corral, selection by use of a lasso, lorry transport and helicopter herding for 1, 2 and 3 days respectively. As control, 9 reindeer were shot without previous handling (in the mountains). The results indicated the traditional selection technique of using a lasso to be the most stressful and glycogen-depleting handling procedure so far studied. In the lasso-selected reindeer the lowest glycogen values and the highest ultimate pH values in the meat were measured. The values of the measured parameters indicating stress (aspartate aminotransferase (ASAT), urea, Cortisol and abomasal lesions) were also highest in these reindeer. By contrast, the modern method of herding by helicopter was not found to be detrimental to glycogen content, ultimate pH, the measured blood metabolites, or the frequency of abomasal lesions. In all treatment groups degenerative lesions were observed in the skeletal muscles. No relarionship between technological and sensory meat quality characteristics and skeletal muscle lesions in reindeer could, however, be found in this study. The study confirmed an earlier finding that a 'stress-flavour' could develop in reindeer meat after intensive pre-slaughter handling of the animals. Further study of when and how such "stress-flavour" develops ought to be undertaken.